Hıristiyan Manastırcılığının Doğuşu - (:unkn) unknown (My University, 2013)
Makalenin amacı Hıristiyan manastırcılığının ortaya çıkışı problemini yapılan yeni çalışmalar ışığında ele almaktır. Manastırlar Hıristiyan asketizminin tatbik edildiği kurumsal yapılardır; bu nedenle ilk olarak asketizm ve manastırcılık ilişkisi ele alınmıştır. Daha sonra özellikle Protestan akademinin tartıştığı menşe probleminin mahiyeti üzerinde durularak, neden özellikle bu konu üzerinde durulduğu sorusuna cevap aranmıştır. Manastırcılığın doğuşu ile ilgili geleneksel teori geniş olarak analiz edilmiş ve ardından bu teori yeni bulgular ve çalışmalar ışığında kritik edilmiştir.

The purpose of this essay is to evaluate the problem of the origins of monasticism in the light of the findings of recent scholarship. Monasteries are institutional bodies to practice Christian asceticism; hence we first discuss the relationship between Christian asceticism and monasteries. We then move on to discuss the problem of the origins of monasticism--raised mainly by the Protestant scholars--and discuss the question why this problem had priority over others. A detailed analysis of the traditional theory for the origins of monasticism will follow. Lastly, we evaluate the traditional theory of monastic origins in the light of the findings of recent scholarship.
The Origins of Christian Monasticism
Keywords: Din Bilimi